2001
DOI: 10.1016/s0735-1097(01)01198-6
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of overutilization and underutilization of thrombolytic therapy in clinical practice

Abstract: With the large benefit known to be associated with thrombolytic therapy and the favorable result of thrombolytic therapy in patients with contraindications observed in this study, we conclude that a formal evaluation of thrombolytic therapy in wider patient categories is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Given the large gains in survival and the relatively small risk of a major bleeding complication, the greater harm would seem to be in undertreating. In a study of 6676 consecutive patients with AMI, Ottesen and colleagues found that the 4-year mortality among the undertreated group was 45.6% as compared with 25.8% among those appropriately treated (risk ratio 0.74, 95% CI 0.60-0.91) with thrombolysis [37]. The 30-day and 4-year mortality among those overtreated was not significantly different than those fulfilling standard criteria and without contraindictions.…”
Section: Clinical Importancementioning
confidence: 98%
“…Given the large gains in survival and the relatively small risk of a major bleeding complication, the greater harm would seem to be in undertreating. In a study of 6676 consecutive patients with AMI, Ottesen and colleagues found that the 4-year mortality among the undertreated group was 45.6% as compared with 25.8% among those appropriately treated (risk ratio 0.74, 95% CI 0.60-0.91) with thrombolysis [37]. The 30-day and 4-year mortality among those overtreated was not significantly different than those fulfilling standard criteria and without contraindictions.…”
Section: Clinical Importancementioning
confidence: 98%
“…Maximising the rate of treatment within existing criteria should be the primary objective, 16 together with greater application of primary angioplasty where appropriate. 17 Nevertheless, on the basis of evidence from other investigators, 12 there may also be a need to extend indications for thrombolysis to patients in whom it would normally be considered inappropriate. Prolonged cardiopulmonary resuscitation, for example, is normally regarded as a contraindication to thrombolysis but a recent study has effectively refuted this.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the TRACE investigators found that "overutilisation" of thrombolytic treatment among patients not fulfilling standard indications was associated with reduced mortality and concluded that treatment should be evaluated in wider patient categories, particularly those with a bleeding risk based on events some time in the past. 12 …”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence for over-utilization of treatments when compared with generally accepted guidelines [14] and underutilization of treatments of demonstrated effectiveness [15]. Variations have been related to local clinical culture [16], the specialty or clinical training of physicians [17], to geography [18], clinical setting, or to socio-economic status, race or ethnicity of the patients [19].…”
Section: Practice Variationmentioning
confidence: 99%